Dark triad personality and cyber-aggression: the mediation of antisocial behaviour - Kong, Kwoi Tat (2023)
The present study aims to investigate the mediating effect of antisocial behaviour on the relationship between the dark triad personality and cyber-aggression. The study had three research objectives which it to investigate the mediating effects of antisocial behaviour on the relationship between (1) Machiavellianism, (2) Psychopathy, and (3) Narcissism on the different types of cyber-aggression (impulsive-appetitive, impulsiveaversive, controlled-appetitive, controlled-aversive). The present study is a quantitative research which uses a cross-sectional research design to collect data from undergraduate students who were currently enrolled in either a public or private university in Malaysia, at least 18 years old, and actively uses social media daily. The present study used the Dirty Dozen Scale, Subtypes of Antisocial Behaviour Scale, and Cyber-Aggression Typology Questionnaire which were distributed using the online survey method. In total, 266 responses were analyzed using Structural Equation Modelling. The results show that there were no mediation effects of antisocial behaviour on the relationships between Machiavellianism and narcissism with all forms of cyber-aggression. However, mediating effects of antisocial behaviour have been found on the relationship between psychopathy and impulsive-appetitive cyberaggression (ab =.524, p <.001), impulsive-aversive cyber-aggression (ab =.489, p <.001), controlled-appetitive cyber-aggression (ab =.552, p <.001), and controlledaversive cyber-aggression (ab =.519, p <.001). The results could be used by mental health professionals to design intervention plans. The results suggest that individuals with high levels of psychopathy would only engage in cyber-aggressive acts if they are involved in antisocial behaviours, effectively making it a risk factor. Therefore, mental health professionals could formulate intervention plans which focus on antisocial behaviour to prevent cyber-aggression amongst individuals with high levels of psychopathy. As only direct relationships were found between Machiavellianism and narcissism and all forms of cyber-aggression, mental health professionals should consider this relationship when trying to identify individuals at risk of engaging in cyber-aggression.